Development of Kasab Tuah Kumita Craft Business in the District Three West Aceh Regency 2007-2024 - Lisa, Fona; Mawardi, Mawardi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Study This aiming to:know the birth process Tuah Kumita Community, know How development The Kumita Community from 2007-2024, and know what is the strategy of the Tuah Kumita Community still exist until now. Research This use method history with approach qualitative. Stages study covering election topic, collection sources, verification, interpretation, and historiography. Data collection techniques are carried out through documentation, interviews. Based on results Research:Tuah Kumita community, founded on January 1, 2007 by Wirda Yanti, aims to... to preserve art Aceh Police Chief and empower Mother House ladder post -tsunami. community This create opportunity Work from House while guard mark culture. The name "Tuah Kumita " symbolizes blessings and spirit resurrection. Tuah Kumita community start develop rapid since 2019 after emit product new such as clothes, skirts, scarves and accessories others, and get support from government. Although face capital and facilities challenges, they Keep going innovate while guard quality and preservation art Acehnese traditional. Strategy to maintain quality and innovation design, continue develop with create new and permanent motifs maintain characteristics typical traditional. They also utilize social media and follow exhibition For expand the market. Although face challenge competition and increase price Ingredients, Kumita Magic still focus on quality product, efficiency production, and creative marketing. Long-term vision long they covers training craftsman new and introducing Chief of Staff of Aceh to level international, while contribute to empowerment economy and conservation culture.